Anti-V2 antibodies virus vulnerability revealed by envelope V1 deletion in HIV vaccine candidates - Isabela Silva de Castro; Giacomo Gorini; Rosemarie Mason; Jason Gorman; Massimiliano Bissa; Mohammad A. Rahman; Anush Arakelyan; Irene Kalisz; Stephen Whitney; Manuel Becerra-Flores; Eric Ni; Kristina Peachman; et al. (iScience, 2021)
Summary: The efficacy of ALVAC-based HIV and SIV vaccines in humans and macaques correlates with antibodies to envelope variable region 2 (V2). We show here that vaccine-induced antibodies to SIV variable region 1 (V1) inhibit anti-V2 antibody-mediated cytotoxicity and reverse their ability to block V2 peptide interaction with the α4β7 integrin. SIV vaccines engineered to delete V1 and favor an α helix, rather than a β sheet V2 conformation, induced V2-specific ADCC correlating with decreased risk of SIV acquisition. Removal of V1 from the HIV-1 clade A/E A244 envelope resulted in decreased binding to antibodies recognizing V2 in the β sheet conformation. Thus, deletion of V1 in HIV envelope immunogens may improve antibody responses to V2 virus vulnerability sites and increase the efficacy of HIV vaccine candidates.